Severe Corrosive Injury Secondary to Chlorine Bleach Ingestion: A Case Report - Yonghoon Choi (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Corrosive injuries to the upper gastrointestinal tract, particularly those caused by alkaline substances, often result in more severe and deeper tissue injuries than those observed after ingestion of acidic substances. We report a case of severe corrosive injury following ingestion of chlorine bleach (200 mL), an alkaline agent. Initial endoscopic evaluation revealed severe esophageal and gastric injuries with necrosis (Zargar grade 3b), without any signs of perforation. The treatment plan included prolonged fasting with total parenteral nutrition, and enteral feeding was initiated via jejunostomy 1 month after hospitalization. The patient was hospitalized and discharged on several occasions until we observed complete healing of the esophagus and stomach. Follow-up endoscopy performed 4 months after the injury showed improvement in the esophageal wall; however, severe stenosis prevented oral intake. Therefore, the patient underwent surgical intervention, including esophagectomy, total gastrectomy, and esophagocolojejunostomy, 7 months post-injury. Since the initial surgery, the patient underwent repeat wound revision procedures, percutaneous drainage, reconstruction, and bougienation owing to anastomotic leakage, infection, and stenosis for approximately a year. The patient received oral and jejunostomy tube feeding for approximately 2.5 years after the initial injury. Early endoscopy was useful to confirm the severity and predict the prognosis of corrosive injuries in this case. Severe corrosive injuries following ingestion of alkaline substances are associated with poor clinical prognosis, as anticipated. Caution is warranted for the diagnosis and treatment of this condition.